2020
DOI: 10.3899/jrheum.190857
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Musculoskeletal Complaints in Patients With Suspected Psoriatic Arthritis and Their Correlation With Physical Examination and Ultrasound

Abstract: Objective To describe the pattern of musculoskeletal symptoms and their correlation with clinical and sonographic findings among psoriasis patients with suspected psoriatic arthritis (PsA). Methods Patients with psoriasis and no prior diagnosis of PsA were referred for assessment of their musculoskeletal complaints. The study included the following steps: 1) assessment by an advanced practice physiotherapist; 2) targeted musculoskeletal ultrasound and 3) assessment by a rheumatologist. In addition, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Furthermore, approximately 70% of the participants advocated for including imaging assessments to confirm ongoing inflammation in the D2T-PsA definition. This emphasis gains relevance in light of recent studies highlighting significant discrepancies between clinical assessments and imaging findings [ 14 ]. Such discrepancies could be attributed to the presence of chronic pain and enthesalgia arising from various aetiologies, such as osteoarthritis or fibromyalgia [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, approximately 70% of the participants advocated for including imaging assessments to confirm ongoing inflammation in the D2T-PsA definition. This emphasis gains relevance in light of recent studies highlighting significant discrepancies between clinical assessments and imaging findings [ 14 ]. Such discrepancies could be attributed to the presence of chronic pain and enthesalgia arising from various aetiologies, such as osteoarthritis or fibromyalgia [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several models of care proposed to improve access to rheumatology care. One model leverages non-physician health care providers (physical therapists, occupational therapists, and nurses with advanced arthritis skills and training) working in expanded scope roles for triage patients with suspected rheumatic disease (18)(19)(20). A systematic review by Desmeules et al showed advanced practice physical therapists provided equal or better care compared to usual care pathways with respect to diagnostic accuracy, treatment effectiveness, use of health care resources, economic costs, and patient satisfaction for patients with musculoskeletal disorders (21).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown to correlate well with magnetic resonance imaging findings and to be more reliable than the physical examination in the assessment of musculoskeletal symptoms (13,14). We previously suggested that MSK‐US may provide additional valuable information to currently used modalities to aid in diagnosing PsA at an earlier stage (15). This highlights the potential use of MSK‐US as point of care for patients at very early stages of their disease; however, the specific role of MSK‐US as a triage tool for patients with suspected PsA has not been widely assessed.…”
Section: Introductionmentioning
confidence: 99%